Mobilizing information for development in the Caribbean: a science and technology perspective - Wiltshire, Winthrop (ACURIL [S.l.], 1993)
Identifies the links between information knowledge and research and perceives science and technology as a interdependent composite which both have the potential to generate useful information as well as to use information to promote problem solving. Stresses that for effective utilization of information to promote development, in relation to science and technology a concomitant is a focus on the development of science and technology per se.